The Taguchi approach to large-scale experimental designs: A powerful and efficient tool for advancing marketing theory and practice - Jordan W. Moffett; Patrick Fennell; Colleen M. Harmeling; Daniel Sheehan; Alexander Bleier (Journal of the Academy of Marketing Science, 2024)
Current research often relies on narrowly focused experimental methods that address just a few independent variables or correlational designs, despite calls for future research to take big-picture perspectives that offer real-world applicability and causal evidence. This disparity likely reflects the constraints imposed by the need for extensive resources to conduct broad, causal examinations. To bridge this gap, the current article presents the Taguchi approach to large-scale experimental design, which remains notably underutilized in marketing research despite being well-established in other fields. Its effectiveness stems from the robust catalog of experimental design rubrics that can incorporate many different independent variables systematically and efficiently. The causal and efficient experimental option for broad scopes of investigation embraces the embeddedness of independent variables and thus can help build marketing theory and advance practice. This article details the fundamentals of the Taguchi approach, its relative advantages, and a three-step implementation process.
Keywords: 330; Experimental design; Hypothesis testing; Taguchi methodology; Fractional factorial design; Marketing theory